2012
DOI: 10.1163/156853812x634035
|View full text |Cite
|
Sign up to set email alerts
|

Optimal egg size in a suboptimal environment: reproductive ecology of female Sonora mud turtles (Kinosternon sonoriense) in central Arizona, USA

Abstract: We studied the reproductive ecology of female Sonora mud turtles (Kinosternon sonoriense) at Montezuma Well, a chemically-challenging natural wetland in central Arizona, USA. Females matured between 115.5 and 125 mm carapace length (CL) and 36-54% produced eggs each year. Eggs were detected in X-radiographs from 23 April-28 September (2007-2008 and the highest proportion (56%) of adult females with eggs occurred in June and July. Clutch frequency was rarely more than once per year. Clutch size was weakly corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…Although PAW scales with shell length close to isometry (i.e., a slope of 1.0), the typical pattern is still hypoallometric. This pattern may simply reflect an ontogenetic elongation of the shell relative to pelvic (i.e., body) width (Brophy, ; Ernst, Wilgenbusch, Boucher, & Sekscienski, ; Fish & Stayton, ; Froese, ; Kamazaki & Matsui, ), and/or adaptive changes in pelvic structure related to locomotion (Lovich et al, ). Because EW scales at only about half the slope as for PAW, the latter probably never constrains egg size in the large turtles of a population (Rollinson & Brooks, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although PAW scales with shell length close to isometry (i.e., a slope of 1.0), the typical pattern is still hypoallometric. This pattern may simply reflect an ontogenetic elongation of the shell relative to pelvic (i.e., body) width (Brophy, ; Ernst, Wilgenbusch, Boucher, & Sekscienski, ; Fish & Stayton, ; Froese, ; Kamazaki & Matsui, ), and/or adaptive changes in pelvic structure related to locomotion (Lovich et al, ). Because EW scales at only about half the slope as for PAW, the latter probably never constrains egg size in the large turtles of a population (Rollinson & Brooks, ).…”
Section: Discussionmentioning
confidence: 99%
“…We investigated the presence of an architectural constraint of the pelvic aperture by conducting analyses of covariance (ANCOVA) to test the homogeneity of slopes between the relationships of pelvic aperture width and mean egg width with CL (see Congdon & Gibbons, ). If slopes are parallel and the largest egg width (x‐radiographed egg width) is larger than the smallest pelvic aperture width in the populations, we concluded that there is a constraint on egg size by the pelvic aperture (Iverson & Smith, ; Lovich, Madrak, et al., ). In these analyses, we used full‐factorial, mixed‐effects regression models via functions from the lme4 package (Bates et al., ) with individual tortoise and year as random effects.…”
Section: Methodsmentioning
confidence: 80%
“…Overall, OES in the Kiawah population appears to represent a combination of scenario 3 (egg size is morphologically constrained until a threshold body size is reached) and scenario 4 (egg size is not morphologically constrained but also not optimized) described in Lovich et al . () because smaller females show evidence of morphological constraint, but larger females do not appear to exhibit canalization around an optimal egg size despite a lack of obvious morphological constraint. OES in the Edisto population appears to best match scenario 4 (egg size is not morphologically constrained but also not optimized) because we did not find evidence for constraint by either aperture, although the variation in egg size could suggest that egg size has not experienced selection pressures sufficiently strong enough to canalize the trait around an optimal value.…”
Section: Discussionmentioning
confidence: 99%
“…C) may account for some deviations from predictions of optimal egg size theory in turtles (Congdon & Gibbons, ; Clark et al ., ). In addition, the diversity of architectures exhibited by the turtle pelvis may also contribute to observed variation (Lovich et al ., ).…”
Section: Introductionmentioning
confidence: 97%